Investigation of bovine viral diarrhoea virus in dairy cattle premises where aborts occur - Gürçay, Metın; İssi, Mustafa; Gül, Yusuf (My University, 2013)
In this study, the presence of Bovine Viral Diarrhoea Virus (BVDV) was investigated by serologic and virologic methods in dairy cattle enterprises where aborts occur. Study materials include 602 blood samples taken from aborted cows and 241 tissue samples taken from waste fetus samples (abortion/stillborn fetus) admitted to the Control Institute of Veterinary Medicine (Elazığ) from dairy cattle enterprises where abort cases were seen in Elazığ, Malatya and Bingöl between September 2011 and April 2012. The lung, liver, spleen and brain tissue samples taken from aborted fetus and blood serum samples were tested by ELISA. With regard to BVDV antibodies, the serum blood samples were founded to be positive in 70.76% (426/602) in total. This ratio was determined as 76.11% (137/180), 56.25% (18/32), 69.48% (271/390) in Elazığ, Malatya and Bingöl provinces, respectively. The prevalence of BVDV antigen in the tissue samples of aborted fetuses was detected as 28.63% (69/241) in total, 25.75% (17/66) in Elazığ, 36.36% (4/11) in Malatya and 29.26% (48/164) in Bingöl.
Keywords: Biyoloji; Mikrobiyoloji; Veterinerlik